VOCABULARY LEARNING STRATEGY USED BY FEMALE STUDENTS OF IAIN SALATIGA MAJORED IN ENGLISH EDUCATION AND TEACHER TRAINING FACULTY: A GENDER PERSPECTIVE - Susanti, Dwi Erna (English Department of Faculty of Tarbiyah and Teacher Training, 2018)
Strategy in learning a language has its? classification on its target skill that will be achieved. One of the target that could be noticed is when language learner intended to posess a varied vocabulary in their mind and to express it appropriately. This study was projected to explore the vocabulary learning strategy applied by the female undergraduate students in an Islamic university. 22 female students involved in the study and they filled up the open-ended questionnaire and engaged in interview to collect the Vocabulary learning strategies. The questionnaire items were adapted from Schmitt taxonomy (2000) which is in English version. The students were facing the fourth semester when the VLS study was conducted. The finding indicated that the variation gender result in the strategy described the general picture of the VLS application in IAIN Salatiga. Each student actually possessed the different characteristics in implementing the VLS and it was not only tied to the gender difference.